Two CIDP Variants Patients With Anti-Caspr1 Antibodies in South China - Li, Chong; Zheng, Hui; Yuan, Chao; Li, Yanran; Hu, Yafang; Jiang, Haishan (Frontiers in Immunology, 2022)
Background and Objectives Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is considered an immune-mediated heterogeneous disease that involves both cellular and humoral immunity. The advent of the new concept of node-paranodopathy in recent years has boosted the identification of more antibody-positive CIDP variants patients. Cases of Caspr1 autoantibodies are the least common. Here, we reported two patients with Caspr1 autoantibodies and summarized their clinical features and treatment responses. Methods Do statistical analyses on the clinical manifestations and laboratory examinations obtained from two patients identified in this study, and eight patients with anti-Caspr1 antibodies reported in previous research. And based on the developed scoring standard, draw the radar charts and line graphs. Results Similar to other studies, the two patients we mentioned had a subacute and severe onset, distal phenotype, sensory ataxia, and severe pain. Differently, they had severe pain accompanying cold sense and coarse tremor in both hands, which may be a typical symptom for the anti-Caspr1 positive patient in south China. And we drew the line and radar graph for two China patients based on five aspects, muscle strength, sensory nerve, cranial nerve, laboratory tests, and NCS examinations. The two visual data charts offered new complementary means for the diagnostic assessment of CIDP variants. Conclusion Pain with cold sense, coarse tremor in hands, and CSF protein levels greater than 3g/L may be the source of the distinct symptoms observed in patients with anti-Caspr1 autoantibodies in south China.